The Prism of Race - Slate, N. author. aut Link
XVII, 246 p.
Keywords: A scholar of race and a leader in the Afro-Asian solidarity movement, Cedric Dover embodied the 20th-century cosmopolitan redefinition of racial identity. Tracing Dover's evolution through his relationships with W.E.B. Du Bois, Langston Hughes, and Paul Robeson, this book tracks racial identity in the twentieth century.